The Effects of Gluten on Weight Gain, Hematological, Biochemical, and Various Endocrinological Parameters - Bektaş, Atilla; Ulusoy, Meltem; Özsarı, Levent; Özel, Ahmet Melih (Turkish Journal of Gastroenterology, 2024)
Background/Aims: This study is aimed to compare the effects of nutrition which has been enriched with different amounts of gluten to gluten-free diets on weight gain, diabetogenic state, hematological, and biochemical parameters. Materials and Methods: A total of 40 newly weaned male Wistar albino rats used in the study were randomized into 4 different groups based on the gluten rations they were given. Following 12 weeks of diet they were killed and intracardiac blood samples were collected. Groups were identified as group 1 (n = 10): control group; normal rat ration containing wheat, group 2 (n = 10): gluten-free diet, group 3 (n = 10): ration containing medium level of gluten (normal rat diet+6% vital gluten) and group 4 (n = 10): ration containing high level of gluten (normal rat diet+12% vital gluten). Results: In groups 3 and 4, high-density lipoprotein was found to be higher than the other 2groups. However, when group 2 results were compared to the other groups; the highest T3, T4, creatinine and B12 levels and the lowest gluten-specific IgE level were observed. alanine aminotransferase and aspartate aminotransferase levels were found to be higher in group 1 compared to the other 3 groups. No statistically significant difference was detected between the groups in terms of other parameters. Conclusion: This study provides evidence that a gluten-containing diet does not cause weight gain, has no diabetogenic effect, and also does not adversely affect general health in relation to hematological, biochemical, and various endocrinological parameters. Cite this article as: Bektaş A, Ulusoy M, özsarı L, özel AM. The effects of gluten on weight gain, hematological, biochemical, and various endocrinological parameters. Turk J Gastroenterol. 2024;35(3):178-185.